2013
DOI: 10.1007/s00125-013-3111-x
|View full text |Cite
|
Sign up to set email alerts
|

A sustained increase in plasma NEFA upregulates the Toll-like receptor network in human muscle

Abstract: Aims/hypothesis Insulin-sensitive tissues (muscle, liver) of individuals with obesity and type 2 diabetes mellitus are in a state of low-grade inflammation, characterised by increased Toll-like receptor (TLR) expression and TLR-driven signalling. However, the cause of this mild inflammatory state is unclear. We tested the hypothesis that a prolonged mild increase in plasma NEFA will increase TLR expression and TLR-driven signalling (nuclear factor κB [NFκB] and mitogen-activated kinase [MAPK]) and impair insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 51 publications
0
27
0
Order By: Relevance
“…During subsequent intravenous insulin stimulation, inhibitory serine-1101 phosphorylation of the insulin receptor substrate-1 (pIRS1-Ser1101) was higher, while phosphatidylinositol 3-kinase (PI3K) and protein kinase B (PKB, Akt) phosphorylation were lower and associated with peripheral insulin resistance (FIGURE 3). Prolonged lipid infusion for 48 -90 h confirmed impaired insulin signaling (231) and stimulated inflammatory pathways, but did not seem to affect DAG, ceramides, or acylcarnitines (179,195). This might be due to the transient nature of the accumulation of lipid metabolites in muscle during lipid infusions (380).…”
Section: Lipid-induced Insulin Resistancementioning
confidence: 85%
“…During subsequent intravenous insulin stimulation, inhibitory serine-1101 phosphorylation of the insulin receptor substrate-1 (pIRS1-Ser1101) was higher, while phosphatidylinositol 3-kinase (PI3K) and protein kinase B (PKB, Akt) phosphorylation were lower and associated with peripheral insulin resistance (FIGURE 3). Prolonged lipid infusion for 48 -90 h confirmed impaired insulin signaling (231) and stimulated inflammatory pathways, but did not seem to affect DAG, ceramides, or acylcarnitines (179,195). This might be due to the transient nature of the accumulation of lipid metabolites in muscle during lipid infusions (380).…”
Section: Lipid-induced Insulin Resistancementioning
confidence: 85%
“…the liver. 38 Therefore, further studies on reducing the side effects of nanomaterial-based products will be of value in this regard. Further studies are suggested to perform reverse verification of TLR5 gene functions, followed by confirming the downstream-signaling pathway with regard to SiNP-induced hyperlipemia and hepatic steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…Potential methods for the contribution of fat to endothelial dysfunction and insulin resistance include inflammation, as some studies demonstrate that infused lipid upregulates Tolllike receptors (22,23), although other studies do not support the involvement of inflammation (20) but cite a metabolic feedback mechanism, as proposed by Randle (34). Lipids have previously been shown to induce insulin resistance by inhibiting glucose transport (37) and reducing nonoxidative glucose disposal (33).…”
Section: Discussionmentioning
confidence: 99%